(untitled) (Texas Journal of Philology, Culture and History, 2023)
This article analyzes Alisher Navoi’s contribution to the development of Uzbek music culture of the 14th-15th centuries, including being a skilled musician, composer, teacher-mentor, and possessing deep knowledge in this field. The information contained in Navoi’s own works and the works of his contemporaries is studied